2017
DOI: 10.1016/j.ijheatmasstransfer.2017.04.077
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty quantification of thermal conductivities from equilibrium molecular dynamics simulations

Abstract: Equilibrium molecular dynamics (EMD) simulations along with the Green-Kubo formula have been widely used to calculate lattice thermal conductivities. Previous studies, however, focused primarily on the calculated thermal conductivities, with the uncertainty of the thermal conductivities remaining poorly understood. In this paper, we study the quantification of the uncertainty by using solid argon, silicon, and germanium as model material systems, and examine the origin of the observed uncertainty. We find that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…To minimize statistical fluctuations, we perform runs for 10 independent ensembles at every temperature. The uncertainty associated with calculation of thermal conductivity from equilibrium MD simulations has recently been quantified by Wang et al 39 who correlated the standard deviation σ κ of the predicted thermal conductivity about the average κ ave , with the total simulation time t total , HCACF correlation time length t corr and number of independent runs N as…”
Section: Molecular Dynamics Simulations Of Lattice Thermal Conducmentioning
confidence: 99%
“…To minimize statistical fluctuations, we perform runs for 10 independent ensembles at every temperature. The uncertainty associated with calculation of thermal conductivity from equilibrium MD simulations has recently been quantified by Wang et al 39 who correlated the standard deviation σ κ of the predicted thermal conductivity about the average κ ave , with the total simulation time t total , HCACF correlation time length t corr and number of independent runs N as…”
Section: Molecular Dynamics Simulations Of Lattice Thermal Conducmentioning
confidence: 99%
“…For each condition, three independent simulations are performed and the average results and their standard deviations are reported. It has been shown that NEMD simulations have much smaller uncertainties than EMD simulations [28]. Whereas the temperature profiles of C1 and C9 exhibit a large temperature jump at the Si/Ge interface and at regions close to the thermal reservoirs, respectively, the temperature profile of C5 is smooth over the entire simulation domain.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence the RGS are ideal objects for comparing experimental data with theory. A large number of experimental [1][2][3][4][5][6][7][8][9] and theoretical [10][11][12][13][14][15][16][17][18][19] studies have been devoted to examination of their thermal conductivity. Initially, a theoretical analysis of the thermal conductivity of dielectric crystals was carried out using the Boltzmann transport equation for phonons [20].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years ab initio calculations of the thermal properties of disordered systems based on the Green Cubo approach using molecular (MMD) or lattice dynamics methods have developed extensively [25][26][27]. This method makes it possible to calculate as well the thermal conductivity of ordered solids, in particular, the thermal conductivity of crystalline argon [14][15][16][17][18][19]. Using MMD and the Green-Kubo method, it was shown that the thermal conductivity of a Lennard-Jones fcc crystal of argon is described by two time constants associated with the attenuation of the autocorrelation function of the heat flow.…”
Section: Introductionmentioning
confidence: 99%